2023
DOI: 10.1021/acsami.2c15980
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Discovery of Novel Garnet-Type Solid-State Electrolyte Candidates via Machine Learning

Abstract: All-solid-state batteries (ASSBs) have attracted considerable attention because of their higher energy density and stability than conventional lithium-ion batteries (LIBs). For the development of promising ASSBs, solid-state electrolytes (SSEs) are essential to achieve structural integrity. Thus, in this study, a machine-learning-based surrogate model was developed to search for ideal garnet-type SSE candidates. The well-known Li 7 La 3 Zr 2 O 12 structure was used as a base material, and 73 chemical elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…We recognized that a method of obtaining ionic conductivity at room temperature by extrapolating a result at high temperature could lead to a significant error for some cases. However, since such a method has been widely employed for this type of research, we strongly believe that current approach is still reliable at least for qualitatively comparing the ionic conductivity values of considered materials.…”
Section: Methodsmentioning
confidence: 99%
“…We recognized that a method of obtaining ionic conductivity at room temperature by extrapolating a result at high temperature could lead to a significant error for some cases. However, since such a method has been widely employed for this type of research, we strongly believe that current approach is still reliable at least for qualitatively comparing the ionic conductivity values of considered materials.…”
Section: Methodsmentioning
confidence: 99%
“…50,54 Therefore, h-MABs are more advantageous in the study of catalytic performance than o-MABs. Moreover, theoretical 55 and experimental 56,57 studies have demonstrated the promising exfoliation feasibility in the M/B = 1:1 family (h-M 2 AB 2 and h-(M′ 2/3 M″ 1/3 ) 2 AB 2 ). In 2020, Rosen and co-workers successfully synthesized twodimensional Mo 4/3 B 2−x and reported their excellent HER catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in combination with DFT and ML, it is possible to investigate the extensive exploration space through employing high-throughput computation for the database construction and surrogate model for rapid inference, thereby accelerating the discovery of promising materials. Thus, in the research field of rechargeable batteries, various studies combining ML and DFT are actively progressing, achieving remarkable outcomes: (1) solid-state electrolyte screening, (2) cathode development, , and (3) anode design are some representative examples.…”
Section: Introductionmentioning
confidence: 99%